2016
DOI: 10.1017/s0031182015001912
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chemical structure of flavanol monomers and condensed tannins onin vitroanthelmintic activity against bovine nematodes

Abstract: SUMMARYPlants containing condensed tannins (CT) may have potential to control gastrointestinal nematodes (GIN) of cattle. The aim was to investigate the anthelmintic activities of four flavan-3-ols, two galloyl derivatives and 14 purified CT fractions, and to define which structural features of CT determine the anti-parasitic effects against the main cattle nematodes. We used in vitro tests targeting L1 larvae (feeding inhibition assay) and adults (motility assay) of Ostertagia ostertagi and Cooperia oncophora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 32 publications
(74 reference statements)
4
41
0
Order By: Relevance
“…Similar findings have been reported with cattle parasites. Condensed tannins composed predominantly of prodelphinidin reduced motility of L1 and adult stage Ostertagia ostertagi and Cooperia oncophora (Desrues et al, 2016).…”
Section: The Anthelmintic Activity Of Condensed Tanninsmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar findings have been reported with cattle parasites. Condensed tannins composed predominantly of prodelphinidin reduced motility of L1 and adult stage Ostertagia ostertagi and Cooperia oncophora (Desrues et al, 2016).…”
Section: The Anthelmintic Activity Of Condensed Tanninsmentioning
confidence: 98%
“…However, Quijada et al (2015) and Desrues et al (2016) reported the opposite effect and suggested that variation in results is likely due to differences and difficulties in extraction and purification of CT, as well as differences in modes of action of different CT on different gastrointestinal nematode parasites. The mode of action of CT on gastrointestinal nematode parasites has not been entirely clarified.…”
Section: The Anthelmintic Activity Of Condensed Tanninsmentioning
confidence: 99%
“…These include inhibition of L3 migration and L4 motility with Ascaris suum, as well as L1 feeding inhibition, adult motility assays of Ostertagia ostertagi and Cooperia oncophora, and larval exsheathment inhibition of Haemonchus contortus and Trichostrongylus colubriformis of L3 larvae (Brunet and Hoste 2006;Quijada et al, 2015;Desrues et al, 2016a;Ramsay et al, 2016). These include inhibition of L3 migration and L4 motility with Ascaris suum, as well as L1 feeding inhibition, adult motility assays of Ostertagia ostertagi and Cooperia oncophora, and larval exsheathment inhibition of Haemonchus contortus and Trichostrongylus colubriformis of L3 larvae (Brunet and Hoste 2006;Quijada et al, 2015;Desrues et al, 2016a;Ramsay et al, 2016).…”
Section: Antiparasitic Effects Of Prodelphinidins and Galloylated Conmentioning
confidence: 99%
“…The average size of CTs in a polymeric mixture (mDP value) can also affect their antiparasitic activity, with larger polymers being more potent against exsheathment of H. contortus L3 and larval feeding of O. ostertagi and C. oncophora L1 larvae in vitro Desrues et al, 2016a). However, PD-rich plants tend to have CTs with high mDP values and high CT concentrations Laaksonen et al, 2015;Mueller-Harvey et al, unpublished data, 2016), confounding our understanding of CT structure-activity relationships.…”
Section: Antiparasitic Effects Of the Mean Degree Of Condensed Tanninmentioning
confidence: 99%
See 1 more Smart Citation